Aplicação do seis sigma no processo de abastecimento de combustível de aeronaves – um estudo de múltiplos casos - Tucci, Henrricco Nieves Pujol (2016)
The aircraft supply is a major cause of flight delays since this process is slow and, if it does not start as soon as the aircraft is available for the maintenance team, the risk of being terminated after the last passenger has already boarded increases. The procedure usually only starts after the information of how much must be supplied get through the flight dispatcher and this information typically take some time to get to the maintenance team. However, it is intended to test a new scenario: start to supply with the minimum quantity of fuel and, if necessary, complete with the amount belatedly informed by dispatcher. Therefore, this paper aims to analyze the application of Six Sigma in this process through the Student's t-test and the Statistical Process Control (SPC). Sigma in this process through the Student t test and Statistical Process Control (SPC). The method adopted was multi cases study by interviews and organizational practices observations. The results showed that the new process is favorable in relation to the former, the Case 1 average time of flight delays has been reduced from 14 to 6 minutes (57%), Case 2 average time has been reduced from 10 to 6 minutes (53%), about flight delays quantity upper than 15 minutes, has reduced to 43% and 39% respectively. It concludes that the application of Six Sigma in aircraft refueling process is innovative to the scientific literature and was favorable for both companies, also helped to mitigate the risk of fines and penalties and, consequently, improved the level of quality of service offered by the airline company.